2019
DOI: 10.1126/sciadv.aax6535
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic efflux of ancient marine dissolved organic carbon in primary marine aerosol

Abstract: Marine refractory dissolved organic carbon is emitted to the atmosphere in primary marine aerosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 41 publications
4
35
1
Order By: Relevance
“…The photic zone contains dissolved organic matter composed of carbohydrates and particles containing viruses, bacteria, algae, and organic dedritus that can bind together by exopolymer gels and contribute to the MBL aerosol budget after bubble bursting (Bigg et al, ; Facchini, Rinaldi, et al, ; Quinn & Bates, ). A large body of work for the WNAO region, including over the Sargasso Sea, provides consensus that primary marine aerosols ejected from the sea surface are highly enriched in marine‐derived organics relative to sea water (Beaupré et al, ; Frossard, Gérard, et al, ; Frossard, Long, et al, ; Keene, Maring, et al, ; Long, Keene, Kieber, et al, ; Quinn et al, ) and that these organic‐laden aerosols are both CCN‐active (Quinn et al, ) and reactive (Zhou et al, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…The photic zone contains dissolved organic matter composed of carbohydrates and particles containing viruses, bacteria, algae, and organic dedritus that can bind together by exopolymer gels and contribute to the MBL aerosol budget after bubble bursting (Bigg et al, ; Facchini, Rinaldi, et al, ; Quinn & Bates, ). A large body of work for the WNAO region, including over the Sargasso Sea, provides consensus that primary marine aerosols ejected from the sea surface are highly enriched in marine‐derived organics relative to sea water (Beaupré et al, ; Frossard, Gérard, et al, ; Frossard, Long, et al, ; Keene, Maring, et al, ; Long, Keene, Kieber, et al, ; Quinn et al, ) and that these organic‐laden aerosols are both CCN‐active (Quinn et al, ) and reactive (Zhou et al, ).…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Between September and October 2016, a research cruise with the R/V Endeavor over the WNAO was conducted to investigate marine aerosol production from bursting bubbles and the physicochemical properties of the generated primary marine aerosol (Beaupré et al, 2019;Frossard, Gérard, et al, 2019;Frossard, Long, et al, 2019). Results from this project have revealed that primarily produced marine aerosols are enriched with marine-derived organic constituents, including surfactants, relative to sea water (Frossard, Gérard, et al, 2019).…”
Section: -2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Marine dissolved organic carbon (DOC) is one of the largest carbon reservoirs on Earth, comparable in size to the reservoir of atmospheric CO 2 (Hansell, 2013). Marine DOC is coupled to the global carbon budget mainly through autotrophic and heterotrophic processes (Benner, 1998) and secondarily through processes that include photochemistry (Mopper et al, 2015), hydrothermal vents (Hawkes et al, 2015; Walter et al, 2018), dissolved and particulate organic carbon interactions and conversions (Druffel & Williams, 1990; Hansell et al, 2009), and primary marine aerosol generation (Beaupré et al, 2019; Kieber et al, 2016) that affect the cycling of DOC in the oceans and the transfer of carbon between the oceans and atmosphere (Siegenthaler & Sarmiento, 1993). It has been shown that sunlight‐mediated DOC photochemistry is an important source of low‐molecular‐weight (LMW) compounds in the surface oceans (Kieber et al, 1989; Miller et al, 2002; Moran & Zepp, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Bulk samples for analysis of surfactants were transferred to precombusted 10 mL Pyrex tubes, stored frozen, and separated with solid phase extraction, and analyzed with ultraviolet‐visible (UV‐Vis) spectroscopy and pendant drop tensiometry following the method described by Gérard et al (). See companion papers (Beaupré et al, ; Frossard et al, ) for additional details regarding methodologies, results, and interpretations of 14 C results and surfactant properties measured in bulk samples of mPMA.…”
Section: Methodsmentioning
confidence: 99%